Litter Decomposition Dynamics Of Quercus semecarpifoHa Forests in Northwest Himalaya - PANWAR, VIJENDER PAL; SIVARANJANI, S.; BALA, NIRMALYA; TOPWAL, R.S. (Indian Forester, 2023)
Litter production and decomposition are fundamental ecosystem processes and plays a key role in nutrient cycling. This study alms to determine the litter decomposition rate and macro nutrient (N, P, K, Ca and Mg) in decomposed litter of Quercus semecarpifbiia. Maximum weight loss due to decomposition was recorded from June to October, and climatic variables significantly affected decomposition. During decomposition nitrogen (1.37-1.89) and phosphorous (0.12-0.14) were increased and gradual decrease in potassium (0.40-0.24), calcium (0.71-0.46) and magnesium (0.22-0.17) concentration was observed. Most of the nutrients were lost during the rainy months (JuneSeptember). Total nutrient return (236.06 l(g ha') was observed from the decomposing litter In the order o f N (101.09) > Ca (78.74) > K (29.94)> Mg (17.36) > P (8.93) through the Input from different components In the order of leaves > twigs > miscellaneous litter > reproductive litter > barlt. Maximum nutrient return was observed from May to July. Out of the total nutrients returned through leaf litter, 75 Vo were released through decomposition, and 25% were accumulated on the forest floor.